2018
DOI: 10.3389/fimmu.2018.01128
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αDβ2 (CD11d/CD18) Modulates Leukocyte Accumulation, Pathogen Clearance, and Pyroptosis in Experimental Salmonella Typhimurium Infection

Abstract: β2 integrins are critical in host defense responses to invading pathogens and inflammation. Previously, we reported that genetic deficiency of integrin αDβ2 in mice altered outcomes in experimental systemic infections including accelerated mortality in animals infected with Salmonella enterica serovar Typhimurium. Here, we show that deficiency of αDβ2 results in impaired accumulation of leukocytes in response to peritoneal infection by S. Typhimurium, impaired pathogen clearance in vivo, defective bacterial el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Thus, CR4 (CD11c/CD18) may be important for the clearance of infections mediated by pathogens that are opsonized by C4 [56,109,195,196]. In a peritoneal Salmonella Typhimurium infection model, CD11d −/− mice were characterized by diminished peritoneal infiltration of leukocytes and accordingly elevated bacterial loads [224]. Ex vivo analysis confirmed attenuated phagocytic activity of CD11d −/− macrophages, accompanied by increased cell death in the course of the inflammatory response, termed pyroptosis [225].…”
Section: Bacterial Infectionsmentioning
confidence: 97%
“…Thus, CR4 (CD11c/CD18) may be important for the clearance of infections mediated by pathogens that are opsonized by C4 [56,109,195,196]. In a peritoneal Salmonella Typhimurium infection model, CD11d −/− mice were characterized by diminished peritoneal infiltration of leukocytes and accordingly elevated bacterial loads [224]. Ex vivo analysis confirmed attenuated phagocytic activity of CD11d −/− macrophages, accompanied by increased cell death in the course of the inflammatory response, termed pyroptosis [225].…”
Section: Bacterial Infectionsmentioning
confidence: 97%
“…7B) that can contribute to the increased mortality of α D ‐deficient mice during endotoxemia. The increased pyroptosis was previously detected in α D ‐deficient macrophages during Salmonella typhimurium infection 46 . Apparently, neutrophils and macrophages have a similar α D β 2 ‐related molecular mechanism for the prevention of pyroptosis during inflammation.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast to these results, a moderate protective effect of D 2 was detected during Salmonella typhimurium infection. 46 Specifically, the authors showed slightly reduced survival of D -deficient mice after Salmonella infection, which correlated with an increased concentration of proinflammatory cytokines, enhanced macrophage pyroptosis and a reduced ability to combat Salmonella in D −/− mice. Notably, the outcome again was associated with macrophage functions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to this original postulate, a study has demonstrated that CD11d/CD18 was not required for clearance of parasitized red blood cells in a murine malaria model ( 38 ). In CD11d -/- mice, peritoneal macrophages have no defect in the internalization of latex beads and phagocytosis of Salmonella Typhimurium ( 103 ). Additionally, a separate study found murine CD11d -/- neutrophils and macrophages have no defect in the phagocytosis of Escherichia Coli ( 76 ).…”
Section: Cd11d In Phagocytosismentioning
confidence: 99%